2020
DOI: 10.3390/ijms21249675
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Insulin-Like Growth Factor I is Involved in the Effect of High Fat Diet on Peripheral Amyloid β Clearance

Abstract: Obesity is a risk factor for Alzheimer’s disease (AD), but underlying mechanisms are not clear. We analyzed peripheral clearance of amyloid β (Aβ) in overweight mice because its systemic elimination may impact brain Aβ load, a major landmark of AD pathology. We also analyzed whether circulating insulin-like growth factor I (IGF-I) intervenes in the effects of overweight as this growth factor modulates brain Aβ clearance and is increased in the serum of overweight mice. Overweight mice showed increased Aβ accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…To elucidate whether 40 Hz light flicker reduces Aβ production, we examined its effects on APP cleavage by measuring levels of the cleavage intermediates of APP, sAPPα, soluble amyloid precursor protein β (sAPPβ), and Aβ in APP/PS1 male mice (Figure 1c). Using the sAPPβ and sAPPα as markers of amyloidogenic and non‐amyloidogenic pathway (Herrero‐Labrador et al, 2020), respectively, we found that stimulation with 40 Hz light flicker significantly reduced sAPPβ (Figure 1d) and Aβ (Figure 1f), but increased sAPPα (Figure 1e) and sAPPα/sAPPβ ratio (Figure g), compared with those of dark control and 80 Hz light flicker. We next determined if 40 Hz light flicker altered APP‐proteolytic processing in APP/PS1 female mice (Figure b).…”
Section: Resultsmentioning
confidence: 80%
“…To elucidate whether 40 Hz light flicker reduces Aβ production, we examined its effects on APP cleavage by measuring levels of the cleavage intermediates of APP, sAPPα, soluble amyloid precursor protein β (sAPPβ), and Aβ in APP/PS1 male mice (Figure 1c). Using the sAPPβ and sAPPα as markers of amyloidogenic and non‐amyloidogenic pathway (Herrero‐Labrador et al, 2020), respectively, we found that stimulation with 40 Hz light flicker significantly reduced sAPPβ (Figure 1d) and Aβ (Figure 1f), but increased sAPPα (Figure 1e) and sAPPα/sAPPβ ratio (Figure g), compared with those of dark control and 80 Hz light flicker. We next determined if 40 Hz light flicker altered APP‐proteolytic processing in APP/PS1 female mice (Figure b).…”
Section: Resultsmentioning
confidence: 80%
“…For example, in a European cohort study, a machine-learning approach identified 347 plasma metabolites associated with early diagnosis in AD with an area under curve (AUC) of about 0.85 ( Stamate et al, 2019 ). In a study of circulating non-coding RNA in patients with AD, 21 disease-related features were identified using RT-qPCR, and 18 strongly correlated features were extracted using statistical learning methods to establish a machine learning model, with an AUC of about 0.86 ( Herrero-Labrador et al, 2020 ). In an AD classifier based on texture features, the researchers modeled the high-level semantic features of MRI with an accuracy of about 85% ( So et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is related to metabolism and synaptic plasticity, whereas IGF-1 supports nerve growth differentiation, synaptic plasticity and neurotransmitter synthesis and release. The development of hyperglycemia and insulin resistance, which often have a metabolic origin due to bad dietary habits, leads to a reduction of IGF-1 production and an impairment of cognitive function ( Anlar et al, 1999 ; Gómez-Pinilla, 2008 ; Torres Aleman, 2012 ; Herrero-Labrador et al, 2020 ).…”
Section: Western Diets: Liver Metabolism and Neurodegenerative Disordersmentioning
confidence: 99%